Stem knowledge in teaching Cosmetology among lecturers in Malaysian vocational colleges - Zakaria, Anis; Jamalluddin, Nor Huda; Abd Wahab, Nabila (Human Resource Management Academic Research Society, 2023)
In the 21st century, STEM elements (Science, Technology, Engineering and Mathematics) have become the norm in education and must be emphasized. This study aims to see the level of knowledge of lecturers, especially lecturers in the field of Cosmetology, in 16 vocational colleges throughout Malaysia, which are divided according to Zones, and to see the extent of the application of STEM elements in the learning and facilitation (PdPc) of Vocational College Cosmetology lecturers. With this study, we see the extent of the involvement of STEM elements in this vocational education, especially in skills. We will also see the importance of STEM elements in vocational education in line with the educational needs of the 21st century. This study seeks the level of lecturers' knowledge and STEM application in teaching and learning. In summary, the study's findings show that only 2.2 were unable to answer the STEM meaning question, and 97.8 were able to answer well and thoroughly. Lecturers first need to know the meaning of STEM and the elements found in it. As for the level of knowledge of STEM elements in each treatment machine, seven machines have been prepared in the question. Findings show the level of application of STEM elements. The findings show that Cosmetology lecturers apply STEM elements in their PDPC, whereas the correlation results show no significant relationship between the two variables.